2023
DOI: 10.1021/acsapm.3c01463
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of High-Molecular-Weight Biobased Polycarbonates by Lithium Lactate

Tingting Wang,
Qiubo Wang,
Ying Quan
et al.

Abstract: Biobased polycarbonates have attracted a wide range of interest due to sustainable resources; however, the synthesis of biobased polycarbonates with a high molecular weight remains a great challenge on account of the influence of catalysts. Herein, biobased poly(isosorbide carbonate) (PIC) with a high molecular weight of 105.0 kDa and excellent light transparency was synthesized via melt polycondensation of isosorbide and diphenyl carbonate by an efficient lithium lactate catalyst under mild conditions, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The conversions of DPC catalyzed by NaOH and Cs 2 CO 3 in the transesterification stage were high enough. However, high molar mass products were not obtained under the conditions, which might be attributed to the strong alkalinity of catalysts, resulting in a high degree of degradation or hydrolyzation of the polymer chain . In addition, the products were dark in color and unsuitable for applications (shown in Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The conversions of DPC catalyzed by NaOH and Cs 2 CO 3 in the transesterification stage were high enough. However, high molar mass products were not obtained under the conditions, which might be attributed to the strong alkalinity of catalysts, resulting in a high degree of degradation or hydrolyzation of the polymer chain . In addition, the products were dark in color and unsuitable for applications (shown in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…30 Several catalysts with alkali metal cation and organic acid anion were selected by Wang et al to synthesize PICs. 37 They found that lithium lactate showed the highest catalytic reactivity, and metal cations and acid anions might have interactions with the oxygen and hydrogen atom in the hydroxyl groups of ISB, respectively. It is noteworthy that high reactivity of alkali metal catalysts usually results in the coloration of PIC products.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations